Analisis Kinerja Anggota DPRD Kabupaten Batu Bara Tahun 2014 - 2019 dalam Pembentukan Peraturan Daerah - Indah Widyastuti; Isnaini Isnaini; Adam Adam (Universitas Medan Area, 2022)
The purpose of this study is: To analyze how the performance analysis of members of the DPRD of Batu Bara Regency in 2014 - 2019 in the Formation of Regional Regulations. The results of research on the performance of DPRD members in Batu Bara Regency in 2014 – 2019 in the Formation of Regional Regulations. The results show that the productivity of DPRD members' performance in carrying out their various functions is not optimal. The quality of service provided by members of the DPRD of Batu Bara Regency has not been optimal and that it runs well in the community where the community assesses the inability of members of the DPRD of Batu Bara Regency to serve their aspirations. The performance of the DPRD members of Batu Bara Regency in accountability has not been running optimally, it can be seen that the community does not yet know what is the function of their performance and have not felt the impact. In terms of responsiveness, the performance of DPRD members in Batu Bara Regency has not been implemented if in the implementation of responsiveness to the community it has not had maximum results such as the weakness in making policies and policies that have not been felt by the people of Batu Bara Regency. Regions The obstacles in carrying out performance as members of the DPRD of Batu Bara Regency are: lack of knowledge of DPRD members of Batu Bara Regency, lack of experience in forming Regional Regulations, lack of mastery of data and information by members of the Regional People's.